Is liquidity associated to profitability? an analysis of the electricity industry in Iberia - Dona, Ricardo Francisco Montenegro (2022)
This paper aims to clarify the relationship between Profitability and Liquidity in the Portuguese and Spanish Electricity industry, using univariate, bivariate, and multivariate statistics. The study is based on a sample of 76 companies, 38 from each country. Regarding the used measures, Return on Assets is the proxy of Profitability and Current Ratio, Quick Ratio, and Cash Ratio are the proxies of Liquidity. According to the results, a positive relationship between Profitability and Liquidity was found. Being the Cash Ratio the one with higher association, meaning that if managers want to increase ROA, increasing Cash Ratio will provide that result.